A Study of Concrete Hydration and Dielectric Relaxation Mechanism Using Ground Penetrating Radar and Short-Time Fourier Transform. (20th July 2010) - Lai, W. L.; Kind, T.; Wiggenhauser, H.
Abstract : Ground penetrating radar (GPR) was used to characterize the frequency-dependent dielectric relaxation phenomena in ordinary Portland cement (OPC) hydration in concrete changing from fresh to hardened state. The study was experimented by measuring the changes of GPR A-scan waveforms over a period of 90 days, and processed the waveforms with short-time Fourier transform (STFT) in joint time-frequency analysis (JTFA) domain rather than a conventional time or frequency domain alone. The signals of the direct wave traveled at the concrete surface and the reflected wave from an embedded steel bar were transformed with STFT, in which the changes of peak frequency over ages were tracked. The peak frequencies were found to increase with ages and the patterns were found to match closely with primarily the well-known OPC hydration process and secondarily, the evaporation effect. The close match is contributed to the simultaneous effects converting free to bound water over time, on both conventional OPC hydration and dielectric relaxation mechanisms.